THE EFFECT OF AUDIOVISUAL ROLE PLAY EDUCATION ON THE LEVEL OF DISASTER KNOWLEDGE IN SMPN 01 BOTUMOITO STUDENTS - Pipin Yunus; Haslinda Damansyah; Ikram Wahyudinn Mantu (LPPM Universitas An Nuur, 2026)
Background: Disaster as an event or series of events that endanger and disrupt the lives and livelihoods of the community. The causes can come from natural factors, non-natural factors, or a mixture of both, which result in loss of human life, environmental damage, material losses, and have an impact on mental health. The purpose of this study is to determine the effect of Audiovisual Role Play Education on the Level of Disaster Knowledge in SMPN 01 Botumoito Students. Methods: Quantitative research design using the One Group Pre-test and Post-Test Approach. Sampling using Purposive Sampling with a sample size of 32 respondents. Data collection techniques using questionnaires and data obtained from schools. Results: The results of this study obtained a good level of student knowledge of 20 respondents in disaster knowledge, a sufficient level of student knowledge was obtained by 1 respondent, and a poor level of student knowledge was obtained by 11 respondents in disaster knowledge. The results of statistical tests using the Paired T-test obtained a p-Value value = 0.00> Value a = <0.05 then Ha is accepted and Ho is rejected. Conclusion: Meaning that there is an influence of audiovisual role play education on the level of disaster knowledge in students of SMPN 01 Botumoito.